1991
DOI: 10.1126/science.1852075
|View full text |Cite
|
Sign up to set email alerts
|

A Calcium-Dependent Protein Kinase with a Regulatory Domain Similar to Calmodulin

Abstract: Calcium can function as a second messenger through stimulation of calcium-dependent protein kinases. A protein kinase that requires calcium but not calmodulin or phospholipids for activity has been purified from soybean. The kinase itself binds calcium with high affinity. A complementary DNA clone for this kinase has been identified; it encodes a protein with a predicted molecular mass of 57,175 daltons. This protein contains a catalytic domain similar to that of calmodulin-dependent kinases and a calmodulin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
309
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 395 publications
(321 citation statements)
references
References 19 publications
8
309
1
3
Order By: Relevance
“…3E), suggesting that the junction domain may be a negative regulatory domain of the kinase. This result is supporting the model of CPKs activation that the binding of Ca 2+ can trigger conformational change of the kinase to release an auto-inhibitor from the active site [25]. In the absence of the calcium-binding Yun WANG et al domain, access to the active site is permanently blocked by the pseudosubstrate auto-inhibitor rendering the enzyme inactive [6].…”
Section: Analysis Of the Kinase Activity Of Ntcpk5 Proteinsupporting
confidence: 81%
“…3E), suggesting that the junction domain may be a negative regulatory domain of the kinase. This result is supporting the model of CPKs activation that the binding of Ca 2+ can trigger conformational change of the kinase to release an auto-inhibitor from the active site [25]. In the absence of the calcium-binding Yun WANG et al domain, access to the active site is permanently blocked by the pseudosubstrate auto-inhibitor rendering the enzyme inactive [6].…”
Section: Analysis Of the Kinase Activity Of Ntcpk5 Proteinsupporting
confidence: 81%
“…Since the direct stimulation of protein kinase activity by calcium is typical of CDPKs (Harper et al 1991;Roberts and Harmon 1992), a mAb directed against the soybean CDPKa (Putnam-Evans et al 1989) was used to immunologically detect related proteins in extracts of Chlamydomonas¯agella. A protein with an apparent MW of 65-kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of the CCK1 junction domain with that of other CDPKs and the relative homologies of the kinase-and calmodulin-like domains. A Three or more identical amino acids in the junction domains of CCK1, CDPKa (Harper et al 1991), AK1 (Harper et al 1993), AtCDPK1 (Urao et al 1994), SPK1 (Kawasaki et al 1993), ZmCDPK (Estruch et al 1994) and DcCDPK (Suen and Choi 1991) are shown. B Phylogenetic relations of the kinase domains of the CDPKs from Chlamydomonas (CCK1), soybean (CDPKa), Arabidopsis (AK1) and carrot (DcCDPK) are shown compared with human PKA, PKCa (Finkenzeller et al 1990), rat MLCK (Roush et al 1988) and mouse calcium/calmodulin-dependent kinase II (Karls et al 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, sequence comparisons showed that TgCDPK4 was most similar to CDPKs of apicomplexan parasites P. falciparum PfCDPK2 (Farper et al, 1997) and E. maxima EmCDPK (Dunn et al, 1996) and plants such as A. thaliana CDPK/AK1 (Harper et al, 1993) and soybean CDPKg. (Harper et al, 1991. The sequence of TgCDPK4 has been deposited in Genbank under the accession number AJ488146.…”
Section: Resultsmentioning
confidence: 99%
“…An unusual class of calcium-dependent protein kinases has been described containing calmodulin-like domains (CDPKs) and the kinases can be activated by calcium in the absence of calmodulin, or phospholipids. First described in plants (Harper et al, 1991) such enzymes have also been identified in algae (Yuasa & Muto, 1992) and in apicomplexan parasites such as Eimeria maxima (Dunn et al, 1996) and P. falciparum (Li et al, 2000; …”
mentioning
confidence: 97%